Global Incidence of Frailty and Prefrailty Among Community-Dwelling Older Adults: A Systematic Review and Meta-analysis - Richard Ofori-Asenso; Ken L. Chin; Mohsen Mazidi; Ella Zomer; Jenni Ilomaki; Andrew R. Zullo; Danijela Gasevic; Zanfina Ademi; Maarit J. Korhonen; Dina LoGiudice; J. Simon Bell; Danny Liew (NLM (Medline), 2025)
Importance  Frailty is a common geriatric syndrome of significant public health importance, yet there is limited understanding of the risk of frailty development at a population level.
Objective  To estimate the global incidence of frailty and prefrailty among community-dwelling adults 60 years or older.
Data Sources  MEDLINE, Embase, PsycINFO, Web of Science, CINAHL Plus, and AMED (Allied and Complementary Medicine Database) were searched from inception to January 2019 without language restrictions using combinations of the keywords frailty, older adults, and incidence. The reference lists of eligible studies were hand searched.
Study Selection  In the systematic review, 2 authors undertook the search, article screening, and study selection. Cohort studies that reported or had sufficient data to compute incidence of frailty or prefrailty among community-dwelling adults 60 years or older at baseline were eligible.
Data Extraction and Synthesis  The methodological quality of included studies was assessed using The Joanna Briggs Institute’s Critical Appraisal Checklist for Prevalence and Incidence Studies. Meta-analysis was conducted using a random-effects (DerSimonian and Laird) model.
Main Outcomes and Measures  Incidence of frailty (defined as new cases of frailty among robust or prefrail individuals) and incidence of prefrailty (defined as new cases of prefrailty among robust individuals), both over a specified duration.
Results  Of 15 176 retrieved references, 46 observational studies involving 120 805 nonfrail (robust or prefrail) participants from 28 countries were included in this systematic review. Among the nonfrail individuals who survived a median follow-up of 3.0 (range, 1.0-11.7) years, 13.6% (13 678 of 100 313) became frail, with the pooled incidence rate being 43.4 (95% CI, 37.3-50.4; I2 = 98.5%) cases per 1000 person-years. The incidence of frailty was significantly higher in prefrail individuals than robust individuals (pooled incidence rates, 62.7 [95% CI, 49.2-79.8; I2 = 97.8%] vs 12.0 [95% CI, 8.2-17.5; I2 = 94.9%] cases per 1000 person-years, respectively; P for difference < .001). Among robust individuals in 21 studies who survived a median follow-up of 2.5 (range, 1.0-10.0) years, 30.9% (9974 of 32 268) became prefrail, with the pooled incidence rate being 150.6 (95% CI, 123.3-184.1; I2 = 98.9%) cases per 1000 person-years. The frailty and prefrailty incidence rates were significantly higher in women than men (frailty: 44.8 [95% CI, 36.7-61.3; I2 = 97.9%] vs 24.3 [95% CI, 19.6-30.1; I2 = 8.94%] cases per 1000 person-years; prefrailty: 173.2 [95% CI, 87.9-341.2; I2 = 99.1%] vs 129.0 [95% CI, 73.8-225.0; I2 = 98.5%] cases per 1000 person-years). The incidence rates varied by diagnostic criteria and country income level. The frailty and prefrailty incidence rates were significantly reduced when accounting for the risk of death.
Conclusions and Relevance  Results of this study suggest that community-dwelling older adults are prone to developing frailty. Increased awareness of the factors that confer high risk of frailty in this population subgroup is vital to inform the design of interventions to prevent frailty and to minimize its consequences.